Cassava drying - Best, R. (International Center for Tropical Agriculture, 1979)
Cassava roots deteriorate rapidly after harvesting and must be chipped and dried to less than 14% moisture content for storage. Drying can be done on the farm, on either concrete floors or inclined mesh trays. Optimum loading rate on concrete is 5-7 kg/m2 and 10-16 kg/m2 on trays, depending on wind speed. Drying time depends on climatic conditions and chip loading rate. With an av day-time temp of less than 23°C and more than 70% RH, drying takes 1-2 days at the lowest loading rates. Tray drying is more advantageous in regions with appreciable wind speeds since the night hours can be used and less manpower is required (chips do not have to be turned and respread). A detailed cost analysis is included, as well as details of the construction of the chipper and accessory equipment.